CPhill

avatar
Nombre de usuarioCPhill
Puntuación115955
Membership
Stats
Preguntas 53
Respuestas 37270

 #1
avatar+115955 
+1

8^x                                  9^(x + y)

________  = 64             ________ =   243           

2^(x + y)                          3^(4y)

 

 

Write the first as                                  Write  the second as

 

(2^3)^x                                                     (3^2)^(x + y)                                                                

________  =   64                                   ____________  =    243                           

2^x * 2^y                                                     3^(4y)

 

2^(3x)                                                        3^(2x) * 3^(2y)

________  =  64                                      _____________   = 243

 2^x * 2^y                                                  3^(2y) * 3^( 2y)                                                   

 

2^(2x)                                                        3^(2x)

_____  =  64                                           ________  =   243

2^y                                                            3^(2y)

 

 

2^(2x - y)  = 2^6                                      3^(2x - 2y)  =  3^5

 

So

 

2x - y  = 6   ⇒   -2x + y = -6   (1)

2x - 2y = 5   (2)

 

add   (1)  and (2)

 

-y  =  -1

y = 1

 

2x - 1  = 6

2x  =  7

x =  7/2

 

2xy  =     2(7/2)(1)   =    7

 

 

cool cool cool

15 ene. 2021